2019
DOI: 10.1111/liv.14074
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral contraceptive pill cessation on hepatocellular adenoma diameter: A retrospective cohort study

Abstract: Background & Aims Hepatocellular adenomas (HCA) are rare, hormone‐driven, benign liver tumours. HCA >50 mm are associated with haemorrhage and malignant transformation. Guidelines recommend cessation of oral contraceptive pills (OCP) for size reduction; however, it is currently unknown how HCA respond to cessation of OCP. We sought to investigate the effect of OCP cessation on HCA size. Methods A retrospective cohort study was performed including HCA patients who stoppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…[ 26 ] In case of AAS-induced HA, discontinuation of AAS may regress the mass and thereby potentially prevent unnecessary hepatic surgery. Martijn et al [ 27 ] stated that 98% of HAs follow this trend, and a conservative approach could lead to HA regression below 50 mm. Moreover, a study of 180 patients diagnosed with HA >5 cm found that 81 patients (45%) treated with conservative therapy reached the clinical regression endpoint of <5 cm after a median of 34 months.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] In case of AAS-induced HA, discontinuation of AAS may regress the mass and thereby potentially prevent unnecessary hepatic surgery. Martijn et al [ 27 ] stated that 98% of HAs follow this trend, and a conservative approach could lead to HA regression below 50 mm. Moreover, a study of 180 patients diagnosed with HA >5 cm found that 81 patients (45%) treated with conservative therapy reached the clinical regression endpoint of <5 cm after a median of 34 months.…”
Section: Discussionmentioning
confidence: 99%
“…Even more so, patients with metabolic syndrome and hepatic adenomas seem to be associated with a higher rate of malignization [8]. The association between oral contraceptive use and metabolic syndrome on one hand and HA on the other tends to prove an important hormonal sensitivity of the tumor (obesity is associated with higher estrogen levels), and this is supported by the fact that adenomas may stop their evolution or even regress as a result of oral contraceptive cessation [15]. In spite of this, immunohistological studies failed to prove the direct effect of these hormones via steroid receptors in normal and adenomatous hepatic tissue, and so the mechanism by which high estrogen levels may cause an adenomatous transformation is still incompletely understood [16].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Apart from estrogen, use of anabolic androgens has also been linked to a higher incidence in HAs, which is being proved not only in body builders but also in patients treated with steroids for Fanconi syndrome, aplastic anemia, etc. Cessation of steroid use has also been linked to regression in size of HAs [15].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital HCA is more common in infants and may stem from the unconnected isolated embryonic hepatocytes. Acquired HCA occurs mostly in young women with a history of oral contraceptive use, with an estimated incidence of 3-4 per 100000 women[1,2]. This may be due to the fact that oral contraceptives promote necrosis of hepatocytes and regeneration of nodules, leading to the development of HCA.…”
Section: Introductionmentioning
confidence: 99%